2020
DOI: 10.1093/jac/dkaa093
|View full text |Cite
|
Sign up to set email alerts
|

The effect of N-acetylcysteine in a combined antibiofilm treatment against antibiotic-resistant Staphylococcus aureus

Abstract: Background The WHO declared Staphylococcus aureus as a ‘pathogen of high importance’ in 2017. One-fifth of all bloodstream-related infections in Australia and 12 000 cases of bacteraemia in the UK (2017–18) were caused by the MRSA variant. To address the need for novel therapies, we investigated several permutations of an innovative combination therapy containing N-acetylcysteine (NAC), an antibiotic and an enzyme of choice in eradicating MRSA and MSSA biofilms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 39 publications
4
30
2
Order By: Relevance
“…This study also showed that NAC degraded secreted and matrix-bound polysaccharides in a strain-dependent manner in the uropathogens tested. This finding has also been observed in other biofilm-forming pathogens, such as S. aureus MSSA and MRSA, P. aeruginosa , and Helicobacter pylori [ 32 , 45 , 46 ]. Degrading polysaccharides required for matrix formation could affect the adhesive properties of the matrix to a surface and subsequent robust biofilm formation [ 36 ], the characteristics of which are especially vital for bacterial survival in the urinary tract given the shear stress bacteria are exposed to by urine flow forces [ 47 ].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This study also showed that NAC degraded secreted and matrix-bound polysaccharides in a strain-dependent manner in the uropathogens tested. This finding has also been observed in other biofilm-forming pathogens, such as S. aureus MSSA and MRSA, P. aeruginosa , and Helicobacter pylori [ 32 , 45 , 46 ]. Degrading polysaccharides required for matrix formation could affect the adhesive properties of the matrix to a surface and subsequent robust biofilm formation [ 36 ], the characteristics of which are especially vital for bacterial survival in the urinary tract given the shear stress bacteria are exposed to by urine flow forces [ 47 ].…”
Section: Discussionsupporting
confidence: 68%
“…The effect of NAC on the initial adhesion of UPEC and E. faecalis was investigated as mentioned previously [ 32 ]. Briefly, six-well plates (Corning Corp., Corning, NY, USA) were seeded with bacteria at a density of OD 600 nm = 0.1 ± 0.02 and incubated for 2 h at 37 °C and 100 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent in vitro studies of N-acetylcysteine efficacy on S. aureus biofilms of six MRSA and six MSSA isolates demonstrated that N-acetylcysteine is equally disruptive against Gram-positive organisms [ 149 ]. Addition of 30 mM N-acetylcysteine alone disrupted the biofilms of all 12 isolates by ≥90%, with a 2–3 log 10 decrease in CFU/mL.…”
Section: Emerging Treatments For Bacterial Infection In Cfmentioning
confidence: 99%